Changes in Parent and Child Skin Carotenoids, Weight, and Dietary Behaviors over Parental Weight Management - Pratt, Keeley J. (Nutrients, 2021)
(1) The objective was to determine changes in parent–child (ages 7–18) dyad skin carotenoids spanning parental participation in a medical weight management program (WMP), and associations with parent BMI, child BMIz, fruit/vegetable intake, and family meals and patterns. (2) The study design was a longitudinal dyadic observational study with assessment at WMP initiation, mid-point (3-months), and conclusion (6-months). Twenty-three dyads initiated the study, 16 provided assessments at 3 months, and 11 at program conclusion. Associations between parent and child carotenoids (dependent variables) and parent BMI, child BMIz, increases in fruit/vegetable intake, and family meals and patterns were analyzed using Pearson’s correlations and independent samples t-tests. Repeated measures ANOVA assessed changes in weight status and carotenoids. (3) Parents experienced significant declines in BMI and skin carotenoid levels over 6 months. Parent and child carotenoids were correlated at each assessment. At initiation, parent BMI and carotenoids were inversely correlated, child carotenoids were associated with increased family meals, and never consuming an evening fast food or restaurant meal were associated with increased parent and child carotenoids. (4) Results demonstrate skin carotenoids are strongly correlated within dyads and may be associated with lower parental BMI and positive family meal practices.